Euclid preparation: LXXXV. Toward a DR1 application of higher-order weak lensing statistics - Vinciguerra, S.; Bouchè, F.; Martinet, N.; Castiblanco, L.; Uhlemann, C.; Pires, S.; Harnois-Déraps, J.; Giocoli, C.; Baldi, M.; Cardone, V. F.; Vadalà, A.; Dagoneau, N.; et al. (EDP Sciences, 2026)
This is the second paper in the HOWLS (higher-order weak lensing statistics) series exploring the usage of non-Gaussian statistics for cosmology inference within Euclid. With respect to our first paper, we develop a full tomographic analysis based on realistic photometric redshifts that allows us to derive Fisher forecasts in the (8, w0) plane for a Euclid-like data release 1 (DR1) setup. We find that the five higher-order statistics (HOS) that satisfy the Gaussian likelihood assumption of the Fisher formalism (one-point probability distribution function, 1-norm, peak counts, Minkowski functionals, and Betti numbers) each outperform the shear two-point correlation functions by a factor of 2.5 on the w0 forecasts, with only marginal improvement when used in combination with two-point estimators, suggesting that every HOS is able to retrieve both the non-Gaussian and Gaussian information of the matter density field. The similar performance of the different estimators is explained by a homogeneous use of multi-scale and tomographic information, optimized to lower computational costs. These results hold for the three mass mapping techniques of the Euclid pipeline, aperture mass, Kaiser-Squires, and Kaiser-Squires plus, and they are unaffected by the application of realistic star masks. Finally, we explored the use of HOS with the Bernardeau-Nishimichi-Taruya (BNT) nulling scheme approach, finding promising results toward applying physical scale cuts to HOS.